Thermolytic reverse electrodialysis heat engine: model development, integration and performance analysis. (1st June 2019) - Giacalone, F.; Vassallo, F.; Griffin, L.; Ferrari, M.C.; Micale, G.; Scargiali, F.; Tamburini, A.; Cipollina, A.
Highlights: An experimentally validated model of a reverse electrodialysis heat engine is presented. Ammonium Bicarbonate-water solutions are considered as working fluid of the system. The effect of the main operating variables on the exergy efficiency is assessed. High-performing membranes lead to overall performance improvements. The multi-column regeneration unit increases the overall performance. Abstract: Salinity gradient heat engines represent an innovative and promising way to convert low-grade heat into electricity by employing salinity gradient technology in a closed-loop configuration. Among the aqueous solutions which can be used as working fluid, ammonium bicarbonate-water solutions appear very promising due to their capability to decompose at low temperature. In this work, an experimentally validated model for a reverse electrodialysis heat engine fed with ammonium bicarbonate-water solutions was developed. The model consists of two validated sub-models purposely integrated, one for the reverse electrodialysis unit and the other for the stripping/absorption regeneration unit. The impact of using current commercial membranes and future enhanced membranes on the efficiency of the system was evaluated, along with the effect of operating and design parameters through sensitivity analyses. Results indicated that exergy efficiency up to 8.5% may be obtained by considering enhanced future membranes and multi-column regeneration units.